The Influence of Strategic Entrepreneurship on Innovation Performance: A Study in the Banking Sector - Dewa Gede Ngurah Harthawan; Avanti Fontana (Universitas KH. Abdul Chalim Mojokerto, 2025)
Companies face uncertainty due to the increasingly dynamic business environment today. As time goes by, a company's business model must be able to adapt to the demands of the business environment so that it can maintain and create opportunities and profits in order to create competitive advantage and wealth. Companies must respond to changes in the business environment quickly and effectively. This study examines the influence of strategic entrepreneurship on innovation performance at a private bank in Indonesia, the result of a merger of several large banks, which is undergoing a digital transformation. With a quantitative approach using the Partial Least Squares (SEM-PLS) structural model, this study tests five hypotheses related to entrepreneurial leadership, entrepreneurial mindset, and entrepreneurial culture. The results show that only entrepreneurial leadership has a significant influence on the innovation performance of Bank X. Meanwhile, entrepreneurial mindset and culture do not have a significant impact. Although the process of exploring and exploiting opportunities through strategy and innovation contributes significantly, overall innovation performance is still not optimal. This study highlights the importance of the role of leadership in overcoming weaknesses in entrepreneurial mindset and culture to encourage innovation in the banking sector. The limitations of this study include data that only comes from one bank and the potential for bias in respondents' answers. Further research is expected to address these limitations and expand the application of the model.